Navigating English in the Workplace: Challenges and Strategies of Indonesian Migrant Workers - Rudiantoro, Yohanes deBritto; da Silva, Anna Marietta (Lingua Cultura, 2025)
The research addressed a lack of studies focusing on Indonesian migrant workers’ personal language learning strategies across diverse host countries. Thus, it aimed to investigate the role of English for Indonesian migrant workers (henceforth, IMW), as well as the challenges related to English language use in their workplaces and how they address these problems. The research employs a qualitative research design, with semi-structured interviews as the primary research instrument. The interviews were conducted with ten Indonesian citizens who were working overseas during the data collection period and agreed to participate in this study. The findings show an awareness of the indispensability of English for effective communication at work and social mobility. However, this awareness emerges through the experience of various linguistic challenges. The experiences ranged from understanding broken, colloquial, and accented English to maximizing English input, such as listening to conversations in movies or English language programs online, taking an English course, and engaging in conversations in English. The research recommends that the authority provide intensive English training that encompasses basic English vocabulary, spoken colloquial English, including English slang, as well as English accents, with an emphasis on developing speaking and communication skills.